URANIUM MINERALIZATION IN PEGMATITES OF THE REGUIBAT SHIELD (TASIAST-TIJIRIT TERRANE), MAURITANIA - Sydorchuk, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Mauritania becomes one of the main stratigic objects of Western Africa as to exploration of the new mineral deposits. Currently active prospecting works are carried out with the participation of foreign companies for such minerals as iron, copper, gold, uranium, diamonds, rare and rareearth elements, etc. Our investigations are carried out within Tasiast-Tijirit terraine, which comprize the North-Western part of Archaean block of the Reguibat shield. The main types of rocks distributed in the terrane are migmatites and ortogneisses, greenstone associations and granitic intrusions. The rocks of this massif are of Mesoarchaean age. In the pegmatite fields, which are distributed among migmatites and amphibolites, the occurrences of uranium mineralization were observed, which is perspective for doing prospection work. The pegmatites show typical medium-coarse-grained structure. Among the the main minerals are plagioclase (oligoclase-albite), quartz, K-feldspar, biotite, garnet, zircon, sphene, monazite, magnetite, ilmenite, uranium and thorium minerals. To determine the morphology and chemical composition of uranium minerals the microprobe analysis was used. The main minerals, which contain uranium are represented by uranophane, uranothorite and brannerite. Uranophane was found in several forms – as secondary mineral, which was formed during metasomatic processes, as dust-shaped mineral associated with small galena grains, and as segregation in structure of solid solution with uranothorite. The last one shows presence of a significant admixture of REE of both cerium and yttrium groups. Brannerite was observed only as dust-shaped mineral at the rims of biotite grains. The results obtained indicate the high potential of the Tasiast-Tijirit terrane for prospecting and exploration of new uranium deposits at this area.
Keywords: microprobe analysis; pegmatites; uranium minerals; Islamic republic of Mauritania